PELAKSANAAN SISTEM LPSE BERDASARKAN PERATURAN PRESIDEN NOMOR 54 TAHUN 2010 TENTANG PENGADAAN BARANG/JASA PEMERINTAH JO. PERATURAN LKPP NOMOR 1 TAHUN 2011 TENTANG TATA CARA E-TENDERING DALAM HUBUNGANNYA DENGAN PENGGUNAAN ANGGARAN YANG EFEKTIF DAN EFISIEN ( - ENDANG MASRONI,SH A.21212067, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2014)
AbstractThe development of science and technology in the field of information influences the law-making process in the procurement of goods / services and look for innovative solosi and to implement the above principles to form a legal product procurement of goods / services, as contained in Presidential Decree No. 54 of 2010, which utilize electronic means of informatics in conducting the procurement of goods / services of the government. In the process of auctions to procure goods and services from government to the provider of goods / services by the private sector (the public), and the system in this way by Presidential Decree No. 54 of 2010 which became one of the innovative legal products procurement of goods and other services, it Procurement embodied in electronic or E-Procurement,Procurement of Goods / Services as set out in Presidential Decree No. 54 Year 2010, (regulation. 54/2010), which is busy discussed among providers of Goods / Services. Is a concrete manifestation of the government's efforts to make prinsif Good Governace and clean Governnment, or a good governance and clean.